2007
DOI: 10.1016/j.semarthrit.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter Reactive Arthritis: A Systematic Review

Abstract: Objective-To review the literature on the epidemiology of Campylobacter associated ReA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(94 citation statements)
references
References 66 publications
1
80
0
7
Order By: Relevance
“…It is likely that C. jejuni's invasive nature and disruption of epithelial barrier integrity combined with the stimulation of host proinflammatory cytokines and defensins play a composite role in gastroenteritis (11,15,37,64). However, our understanding of the sequence of events leading to postinfectious sequelae (for example, reactive arthritis and irritable bowel syndrome), now more frequently being associated with the bacterium (38,51), is minimal. This study identifies and characterizes an IL-6-mediated proinflammatory pathway induced by C. jejuni infections, which has shown significant links to the development of autoimmune and inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that C. jejuni's invasive nature and disruption of epithelial barrier integrity combined with the stimulation of host proinflammatory cytokines and defensins play a composite role in gastroenteritis (11,15,37,64). However, our understanding of the sequence of events leading to postinfectious sequelae (for example, reactive arthritis and irritable bowel syndrome), now more frequently being associated with the bacterium (38,51), is minimal. This study identifies and characterizes an IL-6-mediated proinflammatory pathway induced by C. jejuni infections, which has shown significant links to the development of autoimmune and inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms can begin approximately 1 month following infection and resolve within a year, although in some patients this condition may persist for up to 5 years (256). In 2007, a systematic review by Pope and colleagues reported the incidence of reactive arthritis associated with Campylobacter infection to be 1 to 5% (257). Other studies have estimated the risk of reactive arthritis associated with Campylobacter infection to be 3 to 13%, compared with 0 to 9% for E. coli O157:H7, 2 to 15% for Salmonella, 1 to 10% for Shigella, and 0 to 14% for Yersinia (256).…”
Section: Reactive Arthritismentioning
confidence: 99%
“…The symptoms of campylobacteriosis can range from a mild, watery diarrhea to dysentery, often with abdominal pain and fever (1). Moreover, there are several serious postinfectious complications associated with C. jejuni, including reactive arthritis (38), Guillain-BarrĂ© syndrome (2), and irritable bowel syndrome (35,44).…”
mentioning
confidence: 99%